Analysis of the Influence of Work Shifts on Employee Workload Using the NASA-TLX Methods - Firmansyah, Daffa; Erliana, Cut Ita; Sayuti, Muhammad (International Journal of Engineering, Science and Information Technology, 2025)
The workload workers face can influence their performance and productivity physically and subjectively. Physical workload includes factors such as environmental temperature, noise, and lighting, which affect the worker's health, while subjective workload encompasses time pressure, effort, and stress experienced by the worker. One form of workload that can impact employees is the shift work system, which often leads to physical and psychological fatigue if not correctly managed. This Company, which implements a shift work system in its rubber processing factory, faces employee productivity and health challenges. This study aims to evaluate employees' workload using the NASA-TLX method, which measures six workload dimensions: Mental Demand, Physical Demand, Temporal Demand, Performance, Effort, and Frustration Level. The results of this study are expected to provide insights into the factors affecting employees' workload and offer recommendations for improving the work system to enhance productivity and team member well-being within the Company.